Faktor - faktor yang mempengaruhi migrasi masuk di Kota Jambi (studi kasus etnis Jawa di Kelurahan Buluran Kenali) - Sulung Tino Anggara; Junaidi Junaidi; Yulmardi Yulmardi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
Research objectives: 1) To determine the characteristics of Javanese ethnic groups in Buluran Kenali Village; 2) To find out and analyze the influence of age, origin, education level and length of stay on the income of Javanese ethnic migrant residents in the Buluran Kenali Village. The data used in this study are primary data obtained from survey results by distributing questionnaires and interviews. The analytical method used in this study is descriptive and quantitative analysis methods, using multiple linear regression analysis. The results of this study indicates that the average age of migrants is 44 years old, married with a total of 2 people, education that has completed an average of 10 years comes directly from Java, with the reason of moving to Jambi City due to family invitation and knowing the City Jambi from family/friends. From the results of multiple linear regression it is known that age, origin, level of education, length of stay have an effect on and significantly affect the income of ethnic Javanese migrants in Jambi City. Partially, age, education and length of stay influence and significantly affect the income of Javanese ethnic migrants in Jambi City, while the origin does not affect and the income of ethnic Javanese migrants in Jambi City. Keywords: Migration, Income, Age, Origin, Education Level, Length of Stay.